Will Trent : The Silent Wife - Book 10 - Slaughter, Karin, 1971- (New York, NY : William Morrow, an imprint of HarperCollinsPublishers, 2020)
Investigating a brutal murder that eerily resembles another from years earlier, Will Trent reopens the case of a possibly wrongly convicted prisoner before teaming up with medical examiner Sara Linton to hunt down the true killer.
Keywords: Trent, Will -- (Fictitious character) -- Fiction; Linton, Sara (Fictitious character) -- Fiction; Government investigators -- Fiction; Murder -- Investigation; Fiction; Medical examiners (Law) -- Fiction; Georgia -- Fiction; Thrillers (Fiction); Detective and mystery fiction